Surgical treatment of a Morgagni hernia causing intermittent gastric outlet obstruction. (5th November 2010) - Griffiths, Ewen A; Ellis, Andrew; Mohamed, Ahmed; Tam, Eddie; Ball, Chris S
Abstract : A Morgagni hernia is a rare diaphragmatic hernia which develops through a congenital defect in the retrosternal area, usually on the right hand side. Because of its congenital aetiology, Morgagni hernias are rarely considered in the differential diagnosis of gastric outlet obstruction symptoms in adults. We present a patient with an incarcerated Morgagni hernia who presented with gastric outlet obstruction. A 77-year-old woman presented with symptoms and signs of gastric outlet obstruction, dehydration and acute renal impairment. She was treated by fluid resuscitation and nasogastric tube insertion. Radiological imaging showed a Morgagni hernia containing stomach, omentum and colon. This was treated surgically via an abdominal approach and the defect was closed with mesh. The patient recovered well from this procedure and was discharged. We discuss the anatomy, clinical presentation and surgical treatment of this rare diaphragmatic hernia to raise awareness among surgeons and surgical trainees.